Championing science : communicating your ideas to decision makers - Aines, Roger D., 1958-; Aines, Amy L., 1956- (Oakland, California : University of California Press, 2019)
"Championing Science is a comprehensive guide that helps scientists persuasively communicate complex scientific ideas to decision makers in government, policy, and education. The book provides real-world tactics for scientists to help build vital communication, influence, and emotional intelligence skills that motivate decision makers, with little to no science background, to understand and support their science. Through instruction, interviews, and examples, scientists learn why inspiring decision makers to act requires extracting the essence of scientific findings, crafting understandable messages, simplifying visuals, bridging paradigm gaps, and storytelling. Principles for championing science come to life through stories of science champions such as Robert Millikan, Vannevar Bush, the work between Caltech and MIT, and others. With Championing Science, scientists will effectively learn how to use their communication skills to garner funding, secure future research, and, ultimately, impact policy"--Provided by publisher.
Becoming a champion -- Self-aware and self-correcting: the key to effective communication -- Extracting the essence -- Who's listening? Know your audience -- Why scientists communicate poorly outside their field -- The first two minutes: show your passion -- Crafting key messages and narratives -- The power of language -- Designing effective visuals -- Improving your speaking skills -- Influence and persuasion -- Managing your emotions -- translations, template and white papers -- Strategies for creating successful relationships with sponsors -- Exercises for applying the championing science skills -- High-impact examples of championing for a cause.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 04, 2019).
JSTOR
Keywords: Communication in science; Business communication; Business presentations; Persuasion (Psychology); Information scientifique; Communication dans l'entreprise.; Présentations (Affaires); SCIENCE -- Philosophy & Social Aspects; LANGUAGE ARTS & DISCIPLINES -- Communication Studies; Business communication; Business presentations; Communication in science; Persuasion (Psychology); bridge paradigm gaps; caltech; compelling narratives; complex scientific ideas; craft clear messages; decision makers; education; essential communication; government; guide; help people understand; helping scientists; industry; influence; layman terms; mit; motivate non experts; real world strategies; relationship building skills; robert millikan; scientists; simplify visuals; vannevar bush